Metformin and N-terminal pro B-type natriuretic peptide in type 2 diabetes patients, a post-hoc analysis of a randomized controlled trial. - Wiebe M C Top; Philippe Lehert; Casper G Schalkwijk; Coen D A Stehouwer; Adriaan Kooy (PLoS ONE)
Background Beyond antihyperglycemic effects, metformin may improve cardiovascular outcomes. Patients with type 2 diabetes often have an elevated plasma level of N-terminal pro B-type as a marker of (sub) clinical cardiovascular disease. We studied whether metformin was associated with a reduction in the serum level of N-terminal pro B-type natriuretic peptide (NT-proBNP) in these patients. Methods In the HOME trial 390 insulin-treated patients with type 2 diabetes were randomized to 850 mg metformin or placebo three times daily. Plasma samples were drawn at baseline, 4, 17, 30, 43 and 52 months. In a post-hoc analysis we analyzed the change in NT-proBNP in both groups. We used a longitudinal mixed model analysis adjusting for age, sex and prior cardiovascular disease. In a secondary analysis we assessed a possible immediate treatment effect post baseline. Results Metformin did not affect NT-proBNP levels over time in the primary analysis (-1% [95%CI -4;3, p = 0.62]). In the secondary analysis there was also no sustained time independent immediate treatment effect (initial increase of 17% [95%CI 4;30, p = 0.006] followed by yearly decrease of -4% [95%CI -7;0, p = 0.07]). Conclusions Metformin as compared to placebo did not affect NT-proBNP plasma levels in this 4.3-year placebo-controlled trial. Potential cardioprotective effects of metformin cannot be explained by changes in cardiac pressures or volumes to the extent reflected by NT-proBNP.